2015
DOI: 10.2174/1574888x10666150312102948
|View full text |Cite
|
Sign up to set email alerts
|

Organ Culture Bioreactors – Platforms to Study Human Intervertebral Disc Degeneration and Regenerative Therapy

Abstract: In recent decades the application of bioreactors has revolutionized the concept of culturing tissues and organs that require mechanical loading. In intervertebral disc (IVD) research, collaborative efforts of biomedical engineering, biology and mechatronics have led to the innovation of new loading devices that can maintain viable IVD organ explants from large animals and human cadavers in precisely defined nutritional and mechanical environments over extended culture periods. Particularly in spine and IVD res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 133 publications
(168 reference statements)
2
93
0
Order By: Relevance
“…Organ cultures can bridge basic science with translational medicine and allow in vitro experiments while maintaining cells in their native tissue [39]. NP cultures confined in Dyneema jackets exhibit rather stable characteristics over sustained periods of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ cultures can bridge basic science with translational medicine and allow in vitro experiments while maintaining cells in their native tissue [39]. NP cultures confined in Dyneema jackets exhibit rather stable characteristics over sustained periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike cell cultures, organ culture models retain the native ECM and allow for mechanical loading [39]. Induction of degeneration in these models can be achieved by injection of ECM degrading enzymes such as trypsin [40,41] and papain [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Organ culture models provide a unique platform to bridge from simple cell culture models to in vivo models to study cell behaviour under the native cell microenvironment [12], but one of the limitations of organ culture studies is that the load distribution and the forces that are experienced by the disc cells are unknown. Usually, only the reaction force from the overall loading is recorded.…”
Section: Discussionmentioning
confidence: 99%
“…In short, dynamic and static compression influence disc cell viability, matrix turnover and water content in a magnitude-and duration-dependent manner [5,33]. It has also been demonstrated both in vitro and in vivo that static and dynamic loading affect the homeostasis of the disc matrix by the changes in matrix gene expression over different loading durations [8,12,21]. For instance, Lotz et al found a magnitude-and duration-dependent cell death caused by static compression over 1-7 days in an in vivo rat tail model [19].…”
Section: Introductionmentioning
confidence: 99%
“…To test the performance of the composite hydrogel as a potential NP replacement, we used a bovine ex vivo IVD organ culture model (age of the animals: between 10 and 14 month old), which have been proven to be a adequate option [41,42]. Bovine caudal discs showed to be similar to human IVDs in terms of size, biomechanical behavior and biology [43,44].…”
Section: General Protocolmentioning
confidence: 99%